2022
DOI: 10.1111/and.14385
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pregnancy and time to pregnancy in infertile men with idiopathic oligoasthenospermia pre‐ and post‐coenzyme Q10 therapy

Abstract: Different antioxidants including coenzyme Q10 (CoQ10) have been tried to treat idiopathic male infertility (IMI) with variable results. Therefore, this study aimed to determine the clinical and biochemical predictors of pregnancy outcome and time to pregnancy (TTP) in infertile men with idiopathic oligoasthenospermia (OA) pre-and post-CoQ10 therapy. This prospective controlled clinical study included 178 male patients with idiopathic OA and 84 fertile men (controls). Patients received 200 mg of oral CoQ10 once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…As previously reported, Alahmar et al [ 36 ] investigated the effect of 200 mg CoQ10 for 6 months in 78 iOA infertile men vs. controls. Treatment significantly improved semen parameters, antioxidant biomarkers and SDF.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As previously reported, Alahmar et al [ 36 ] investigated the effect of 200 mg CoQ10 for 6 months in 78 iOA infertile men vs. controls. Treatment significantly improved semen parameters, antioxidant biomarkers and SDF.…”
Section: Resultsmentioning
confidence: 98%
“…More recently, a prospective study investigated 78 patients with idiopathic OA treated with 200 mg of CoQ10 for 6 months and 84 fertile men (controls) [ 36 ]. The authors found that treatment improved semen parameters and antioxidant measures and reduced SDF in infertile participants.…”
Section: Resultsmentioning
confidence: 99%
“…Although some antioxidant combinations positively impacted semen quality, the differences were generally minor, and no significant change in pregnancy rates was detected, probably due to their small sample size. L-carnitine, N-acetylcysteine (NAC) [ 111 , 112 , 113 , 129 , 130 ], coenzyme Q10 [ 114 , 115 ], and vitamin D [ 116 ] were some of the antioxidant combinations used in these studies with a positive impact on semen quality.…”
Section: Antioxidants and Male Infertility—what Is Currently Known?mentioning
confidence: 99%
“…These studies were small scale, and although some combinations did demonstrate an improvement in semen parameters, the differences tended to be small, and no studies demonstrated a significant difference in pregnancy rates. The antioxidant combinations, which showed improvement in sperm parameters include CoQ10 [11 ▪ ,12 ▪ ], l -carnitine, N-acetyl-cysteine [13 ▪ ,14 ▪ ,15 ▪ ,16 ▪ ,17], and vitamin D [18 ▪ ].…”
Section: Medical Treatmentsmentioning
confidence: 99%